Evaluation of Schneiderian First-rank Symptoms in Patients of Psychosis Attending a Tertiary Care Center from North India - Aditi Jain; Abbas Mehdi (Annals of Indian Psychiatry)
Background: The Schneiderian first-rank symptoms (SFRS) have played an extremely important role in the diagnostic systems in psychiatry. However, all studies do not seem to support Schneider’s claim that FRS confer a clear indication of schizophrenia when no organic syndrome is present. Objectives: The objectives of this study were as follows: (1) to examine the presence of SFRS in untreated cases of psychosis, (2) to see the degree of improvement in SFRS with treatment over 12 weeks of short-term follow-up, (3) to see correlation of SFRS with sociodemographic and clinical parameters in our patients, and (4) to see the correlation of SFRS among diagnostic subgroups in our patients. Materials and Methods: Setting: Psychiatry department of a multi specialty tertiary care center in North India. Study Design: This was a short-term prospective study. After taking ethical clearance from the institutional ethics committee and written informed consent from all the patients, data sets were prepared for 60 patients of untreated psychosis. Data analysis was done using the SPSS version 20.0. Results: Voices discussing (83.33%) and voices commenting (80%) were the most commonly noted SFRS, and the mean number of SFRS in our sample was 3.34. Somatic passivity (f = 10.80, P = 0.0001) and thought insertion (f = 6.75 and P = 0.004) could significantly differentiate between schizophrenia and other diagnostic subgroups of untreated psychosis in our study. Conclusions: Only somatic passivity, delusional perception, and thought insertion were extremely specific in distinguishing the patients of schizophrenia from nonschizophrenic patients.